The impact of age on outcomes of coronary artery bypass grafting - Lemaire, Anthony (J Cardiothorac Surg, 2020)
OBJECTIVE: As the population ages, increasing number of older patients are undergoing adult cardiac surgery. The purpose of the study is to assess the impact of age on postoperative outcomes in patients that undergo coronary artery bypass grafting (CABG). METHODS: Patients that are ≥70 years old who underwent CABG were selected from the Nationwide/National Inpatient Sample from 2010 to 2015 using ICD-9-CM diagnosis and procedure codes. The patients who were 70–79 years old were compared to patients aged 80–89 years old to determine if the age difference of the patients had an impact on surgical outcomes. In addition, a secondary endpoint is to compare surgical outcomes between the 2 genders of the patients 80–89 years old. The rates of postoperative complications, and mortality were compared. RESULTS: A total of 67,568 patients were identified who were ≥ 70 years old and underwent CABG. Compared to the Septuagenarians, the Octogenarians were more likely to develop cardiac complications (OR [odds ratio] =1.20, 95% CI [confidence interval] 1.12–1.23. They were also more likely to develop renal complications (P < 0001), and respiratory complications (P < 0001). The Octogenarians were also more likely to bleed postoperatively (P < 0.0001) and have a higher mortality (P < 0001). Furthermore, the female Octogenarians had a higher mortality (OR 1.25 95% CI 1.07–1.46) compared to males in the same age group. CONCLUSIONS: The patients who were ≥ 80–89 years old had worse postoperative outcomes. The Octogenarians who were females had a higher mortality compared to their male counterparts.